Integrative-Interconnective Approaches in Al-Islam and Muhammadiyah Education: Advancing the SDGs at UMS - Hartono; Islah Gusmian; Giyoto (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study examines the implementation of Al-Islam and Kemuhammadiyahan (AIK) with an integration-interconnection approach at the University of Muhammadiyah Surakarta (UMS) and its contribution to SDG 4 (quality education), SDG 16 (peace and justice), and SDG 17 (global partnership). Theoretical framework: The theoretical framework is based on KH Ahmad Dahlan's thoughts on modern Islamic education, the concept of integration-interconnection of knowledge, contextual curriculum theory, the warning of